Ectopic Eruption of the Maxillary Permanent First Molar: a Brief Review and Clinical Case Report - de Mendonça, Marcos Rogério; Fuziy, César Henrique Fukuji; Ferreira, Mayra Fernanda; Delbem, Alberto Carlos Botazzo (ARCHIVES OF HEALTH INVESTIGATION, 2023)
The Ectopic Eruption of the Maxillary Permanent First Molar (EEMPFM) is an eruption anomaly, characterized for the maxillary permanent first molar’s impaction in the distal surface of the deciduous second molar. The etiology is related with change of the axial axis of eruption of the permanent first molar associated with missing space in the maxilla. The diagnosis is the combination of clinical and complementary examination. There are two types of Ectopic Eruption: the reversible and the irreversible. The irreversible type requires orthodontics treatment, because it causes root resorption of the deciduous second molar, causing its premature loss. For the treatment, procedures can be used with the aim of promoting distal inclination of the ectopic first molar, using separator elastics, removable or fixed appliances. The aim of this work is to report a clinical case of a patient of 9 years and 6 months old, female gender, who attended the Clinic presenting EEMPFM of the maxillary right permanent first molar. The treatment was a removable appliance composed with an acrylic base plate with clasps and a finger spring activated against a resin button bonded on the mesiobuccal cusp of the maxillary right permanent first molar. The correction of this anomaly was obtained with 35 days of treatment. Therefore, the sequence of procedures from diagnosis to the indication of an adequate treatment method is fundamental to obtain satisfactory results.